Formulation and Evaluation of Lipid Nanogel Loaded with Quercetin and Curcumin for Improvement of Topical Bioavailability - Iqubal, Mohammad Kashif; Md, Shadab; Ali, Javed; Baboota, Sanjula (Indian Journal of Pharmaceutical Education and Research, 2025)
Aims The present work was aimed to develop and optimize the QCN and CRN-loaded combinatorial NLC (QC-NLC) gel through the Central Composite Rotatable Design (CCRD) for bioavailability improvement of QCN and CRN in the management of skin cancer after its topical application. Materials and Methods After the compatibility study and selection of excipients, CCRD was run and thirteen formulae were obtained. Optimization was completed against particle size, PDI and entrapment efficiency. QC-NLC nanogel was prepared from the optimized combinatorial NLC formulation and evaluated on different parameters, such as homogeneity, spreadability, extrudability, pH, drug content, drug release, permeation, dermatokinetic, stability, etc., Results Developed combinatorial NLCs were optimized based on the particle size (163.8±1.5 nm), PDI (0.28±0.04), and surface charge of optimized NLC was recorded -31.6±1.4 mV. TEM image showed spherical-shaped particles. NLC-based nanogel showed a pH of 6.93±0.59, drug content of 100.85±4.07% QCN and 98.41±5.15% CRN and it exhibited a smooth homogenous characteristic. The nanogel demonstrated a lower value of extrudability than conventional gel, which offers an advantage over the conventional gel. The release profile showed higher drug release from nanogel in a prolonged manner. The permeation and dermatokinetic studies exhibited higher flux and drug distribution ability in the epidermis and dermis layers of skin than conventional gel and it has been further confirmed by the depth analysis using confocal microscopy. Stability studies showed a surpassing storage ability of developed nanogel. Conclusion The topically applied developed nanogel could be a potential approach for skin cancer treatment due to its appreciably improved bioavailability ability in the layers of skin.
Keywords: Combination therapy; Dermatokinetics; Design of experiment; Extrudability; Lipid nanocarrier.